Pro-Kontra Normalisasi Hubungan Diplomatik Israel-Sudan - Muhammad Bachrul Ulum (Jurnal ICMES, 2021)
In 2020, four Arab countries normalized relations with Israel, namely the United Arab Emirates (UAE), Bahrain, Sudan and Morocco. Sudan has been known as a country carrying hard-line Pan-Islamism during the reign of Omar Al-Bashir, so the normalization of relations with Israel is very surprising. Aim of this study is explaining the reasons behind Sudan's agreement to the normalization offer from the US. This study uses a qualitative method with a historical approach to trace the normalization causes and utilizes the concept of "national interest" in foreign policy. This study concludes that Sudan's willingness to normalize its relations with Israel is part of the country's efforts to get off the United States' list of State-Supported Terrorism. The Sudanese government has considered this status as a threat to their national interests, especially in the economic field.